Implementasi Kebijakan District Public Private Mix (DPPM) Dalam Penanganan Tuberculosis di Kota Tasikmalaya Pada Masa Pandemi Covid-19 - Wahono, Tri (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2024)
During this pandemic, reports related to the treatment of Tuberculosis in Tasikmalaya were associated with the public's preference for treatment at private health facilities and the limited availability of Tuberculosis services at public health centers. Built upon these reports, this study aims to provide an overview of the implementation of policies related to the treatment of Tuberculosis in Tasikmalaya during the COVID-19 pandemic. This is qualitative research conducted using in-depth interviews with key informants using interview guidelines that were thematically arranged. Determination of informants in this study using purposive sampling. In-depth interviews were carried out in stages: at the provincial, city, sub-district, and kelurahan levels to obtain an overall picture of TB treatment in the research area. Data were analyzed by using content analysis techniques. The result showed that resource support in the form of budget, facilities, and infrastructure is available but not optimally sufficient for the TB treatment program, while HR is also still experiencing shortages due to the division of tasks for COVID-19. In addition, the increase in human resource capacity cannot be carried out due to a ban on offline activities during the pandemic. Cooperation between government and private health facilities has been initiated, including the formation of DOTS in private health facilities (clinics, private hospitals), although only a small part. Development activities (monitoring and evaluation) related to DPPM network services have not been carried out optimally, this is because there is no activity plan for each team within the organization. This study concludes that efforts to treat Tuberculosis in Tasikmalaya during the COVID-19 pandemic are still ongoing, but in optimally functioned.